Beyond Balanced Growth: On the Analysis of Growth Trajectories - Karl-Josef Koch (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2002)
The core of the analysis of endogenous growth models typically is the examination optimality and stability of balanced growth trajectories. But the development of a robust and general economic theory of endogenous growth around this concept is limited by the lack of simple tools of analysis. In the paper we broaden the concept of balanced growth and propose two new methods of analysis. The first one invokes the theory of time varying systems and the second one is a compactification approach. Both methods are designed to clarify to what extent the linearization of the system along a path of balanced growth reveals enough information about the dynamics in a neighborhood of the path.
Keywords: 330